PENGARUH PROVING GOAL ORIENTATION DAN SELLING EXPERIENCE TERHADAP KINERJA TENAGA PENJUALAN DENGAN PERILAKU PENJUALAN ADAPTIF SEBAGAI VARIABEL MEDIASI (Studi pada Lembaga Keuangan Mikro di Kabupaten Kebumen) - Harini Abrilia Setyawati; Irfan Helmy (Pro Bisnis, 2018)
The purpose of this study was to examine the effect of proving goal orientation (PGO) and selling experience on salesperson performance through adaptive selling behavior. This research was conducted on the sales force in micro finance institution in Kebumen. This study was tested using a quantitative approach with the SmartPLS 3 analysis software tool. The results showed that PGO and adaptive behavior have an effect on salesperson performance. In contrast, work experience has no effect on salesperson performance. This study also examines the influence of PGO and selling experience on adaptive selling behavior. Adaptive selling behavior, proved to mediate the relationship between PGO and selling experience toward salesperson performance.